The Result Discrepancies between Histological and PCR Method for Detecting Helicobacter pylori in Patients with Dyspepsia due to Inappropriate Preparation before Endoscopy - Maruni Wiwin Diarti; Haris Widita; Soewignjo Soemohardjo; Weny Astuti; Troef Sumarno; Yunan Jiwintarum; Zainul Mutaqin; Retno Handayani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: False negative result of Helicobacter pylori (H. pylori) detection in gastric tissue can be due to inappropriate preparation before endoscopy. The objectives of this study is to compare the result of H. pylori detection in gastric biopsy by histological method and ure C polymerase chain reaction (PCR) in patients with dyspepsia who underwent upper gastrointestinal (GI) endoscopy without preparations other than six hours fasting before endoscopy. Method: We obtained 156 paraffin blocks of gastric endoscopic biopsy samples, taken from antrum and corpus of patients with dyspepsia who underwent endoscopic examination at the Endoscopy Unit of Biomedika hospital, Mataram. All biopsy samples were stained with Hematoxylin and Eosin for tissue diagnosis and Giemsa stain for detecting H. pylori Ure C PCR were done on all blocks. Cag PCR were performed on all Ure C PCR positive samples. Results: Of 156 paraffin blocks, only 17 blocks (10.9%) were positive for H. pylori by histological examination. All of the 17 samples showed positive results on PCR method. Of 156 paraffin blocks, positive results were found in 73 patients (45.9%) by ure C PCR method. The PCR method has increased the positivity rates of H. pylori more than four times compared to histological method. This study showed that the rate of cag a was 63.0%. Conclusion: Ure C PCR is superior to histological examination in patients who did not stop consuming acid supressor drug and antibiotic two weeks prior to endoscopy. This phenomenon can be explained by the change of spiral form into coccoid form of H. pylori, which is hardly detected using Giemsa stain.   Keywords: Helicobacter pylori, histology, ureC, Cag a, PCR